Analisis Strategi Penanganan Pembiayaan Fasilitas Likuiditas Pembiayaan Perumahan (FLPP) Bermasalah pada Akad Murabahah di Bank Syariah Indonesia (BSI) Kcp Jambi Hayam Wuruk - Mahathir Hefrianda; Rubiyanto Rubiyanto; Dara Amiati; Okta Trisnawati; Titin Agustin Nengsih; Novi Mubyarto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The Housing Financing Liquidity Facility (FLPP) is a government program designed to provide affordable housing for Low-Income Communities (MBR). In practice, FLPP financing implemented through murabahah contracts is exposed to the risk of non-performing financing (NPF). This study aims to identify the factors causing problematic FLPP financing and analyze the handling strategies implemented by Bank Syariah Indonesia (BSI) KCP Jambi Hayam Wuruk. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that problematic financing is caused by internal factors, including low payment discipline and customer moral hazard, as well as external factors such as declining income due to economic instability. The handling strategies implemented include intensive collection efforts, persuasive approaches, periodic monitoring, and financing restructuring in accordance with Islamic principles. These strategies contribute to maintaining financing quality while providing protection for customers experiencing financial difficulties.